Sistem Informasi Pendataan Penerimaan Bantuan Bedah Rumah pada Desa Barusjahe Kabupaten Karo Berbasis Web - Sembiring, Yasma Aprilyani; Roni J. Simamora; Rimbun Siringoringo; Jamaluddin, Jamaluddin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Data collection for housing renovation assistance in Barusjahe Village is still done manually, resulting in frequent data errors, slow processes, and a lack of transparency. This study developed a web-based data collection information system using the Waterfall method through the stages of analysis, design, implementation, and testing. The system was built with PHP and MySQL and provides features for online registration, file uploads, admin verification, and automatic reports. Testing results show that the system runs well and is able to speed up the data collection process and improve accuracy and convenience for the community and village officials.